HEPATOPROTECTIVE ACTIVITY OF ETHANOLIC STEM BARK EXTRACT OF KNEMA ATTENUATA (HOO K. F. AND THOMSON) WARB - H., SUPRIYA RAJA (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: To investigate the hepatoprotective activity of ethanolic stem bark extract (ESBE) of Knema attenuata against carbon tetrachloride (CCl4) induced hepatotoxicity in Wistar rats using both in vivo and in vitro models. Methods: Animals were treated orally with ESBE (250 mg kg-1 and 500 mg kg-1) once daily for 6 d and CCl4 on the 4th d. On the 7th d, animals were sacrificed and the blood samples were collected to measure the serum levels of biochemical parameters, whereas the liver homogenates were utilized for estimating the antioxidant defense. The hepatoprotective efficacy of the extract was further ensured in vitro using human liver hepatocellular carcinoma (HepG2) cell line against CCl4 induced toxicity. The cell line viability was determined using 3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. Results: ESBE effectively reduced (p<0.001) the elevated serum levels of Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), and Alkaline phosphatase (ALP) when compared to the toxicant control group. ESBE 500 mg kg-1significantly raised the antioxidant defense (p<0.0001) by reducing the malondialdehyde (MDA) level and enhancing hepatic reduced glutathione (GSH) level in comparison to the CCl4 control group. The in vitro effect was investigated using CCl4 exposed HepG2 cells. Pretreatment with ESBE showed a dose-dependent increase in percentage cell viability ranged between 44 to 57% at 12.5-100 μg ml-1concentrations (p<0.001, when compared to the control cells). Conclusion: Present study confirms the hepatoprotective activity of the stem bark extract of K. attenuata against CCl4‑induced liver damage.